1994
DOI: 10.1183/09031936.94.07040730
|View full text |Cite
|
Sign up to set email alerts
|

Arterial oxygenation does not predict the outcome of patients with acute respiratory failure needing mechanical ventilation

Abstract: A Ar rt te er ri ia al l o ox xy yg ge en na at ti io on n d do oe es s n no ot t p pr re ed di ic ct t t th he e o ou ut tc co om me e o of f p pa at ti ie en nt ts s w wi it th h a ac cu ut te e r re es sp pi ir ra at to or ry y f fa ai il lu ur re e Using a discriminant multivariate analysis, the following variables were selected as the best predictors of outcome: 1) the number of associated complications (NAC) on admission; 2) the simplified acute physiologic score (SAPS); 3) oxygenation index (PAO 2 -AaPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 25 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…Age, APS and presence of chronic disease were associated with mortality in non-ARDS, while the initial severity of oxygenation defect was not. This is in agreement with findings by JimØnez and co-workers [5]. They found that the major condition influencing ICU mortality in patients with ARF was the severity of acute illness at admission and that the best predictor for survival was the number of as-sociated complications on admission, simplified acute physiology score (SAPS) and age.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Age, APS and presence of chronic disease were associated with mortality in non-ARDS, while the initial severity of oxygenation defect was not. This is in agreement with findings by JimØnez and co-workers [5]. They found that the major condition influencing ICU mortality in patients with ARF was the severity of acute illness at admission and that the best predictor for survival was the number of as-sociated complications on admission, simplified acute physiology score (SAPS) and age.…”
Section: Discussionsupporting
confidence: 92%
“…One of the reasons for this finding may be that they studied medical ICU patients, who may have a larger prevalence of co-morbidities than our mixed ICU population. Others have also shown the independently predictive contribution of severity of disease scoring in both non-ARDS [5] and ARDS patients [15].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[ 36 ] Some studies failed to show any association between PaO 2 /FiO 2 ratio and mortality. [ 8 25 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…Some studies failed to show any association between Pao2/Fio2 ratio and mortality. [49][50][51] was associated with a survival rate of less than 20% while peak inspiratory pressure of less than 30 cmH2o was associated with a survival rate of 60%. 52 Our study revealed an independent association between plateau pressure of more than 35cmH2o and decreased survival 53 Hill, and Holanda, et al, demonstrated in their study that nasal bridge injury is a common problem with NIMV.…”
Section: Table-imentioning
confidence: 92%